PAX9 polymorphism and susceptibility to sporadic non-syndromic severe anodontia: a case-control study in southwest China - Jing WANG; Yuanzhi XU; Jing CHEN; Feiyu WANG; Renhuan HUANG; Songtao WU; Linjing SHU; Jingyi QIU; Zhi YANG; Junjie XUE; Raorao WANG; Jilin ZHAO; et al. (University of São Paulo, 2013)
Our research aimed to look into the clinical traits and genetic mutations in sporadic non-syndromic anodontia and to gain insight into the role of mutations of PAX9, MSX1, AXIN2 and EDA in anodontia phenotypes, especially for the PAX9. Material and Methods The female proband and her family members from the ethnic Han families underwent complete oral examinations and received a retrospective review. Venous blood samples were obtained to screen variants in the PAX9, MSX1, AXIN2, and EDA genes. A case-control study was performed on 50 subjects with sporadic tooth agenesis (cases) and 100 healthy controls, which genotyped a PAX9 gene polymorphism (rs4904210). Results Intra-oral and panoramic radiographs revealed that the female proband had anodontia denoted by the complete absence of teeth in both the primary and secondary dentitions, while all her family members maintained normal dentitions. Detected in the female proband were variants of the PAX9 and AXIN2 including A240P (rs4904210) of the PAX9, c.148C>T (rs2240308), c.1365A>G (rs9915936) and c.1386C>T (rs1133683) of the AXIN2. The same variants were present in her unaffected younger brother. The PAX9 variations were in a different state in her parents. Mutations in the MSX1 and EDA genes were not identified. No significant diferences were found in the allele and genotype frequencies of the PAX9 polymorphism between the controls and the subjects with sporadic tooth agenesis. Conclusions These results suggest that the association of A240P with sporadic tooth agenesis still remains obscure, especially for different populations. The genotype/phenotype correlation in congenital anodontia should be verified.